Famotidine has a neuroprotective effect on MK-801 induced toxicity via the Akt/GSK-3 beta/beta-catenin signaling pathway in the SH-SY5Y cell line - ARICIOĞLU, FEYZA (ELSEVIER IRELAND LTD, 2019)
Schizophrenia cannot be treated sufficiently with existing antipsychotic drugs. Taken into account that increased Glycogen Synthase Kinase 3 Beta (GSK-3 beta) activity is associated with schizophrenia pathophysiology and certain antipsychotics can be able to decrease GSK3 beta activity, inhibition of GSK-3 beta activity could be a novel approach for the treatment of schizophrenia. In the present study MK-801, a widely used chemical for the in vivo/in vitro modeling of schizophrenia was selected to evoke a detrimental effect on cellular survival via GSK3 beta and related proteins. A limited number of studies have reported the curative effects of famotidine, an antiulcer drug, in schizophrenic patients. To the best of our knowledge, no study investigated the molecular mechanism of the beneficial effect of famotidine in the patients. A recent study based on computerized drug modeling software (docking) indicated that famotidine might inhibit the GSK3 beta activity due to its chemical structure independent from histaminergic receptors. In this study, we aimed to investigate the effects of famotidine on the Akt/GSK-3 beta/beta-catenin signaling pathway on SH-SY5Y neuroblastoma cells in the presence of MK-801. We investigated the effects of famotidine, olanzapine (an antipsychotic drug), and SB 415286 (specific GSK-3 beta inhibitor), on the basal cellular survival and MK-801 induced neuronal death beside of Akt/GSK-3 beta/beta-catenin protein and gene expressions in SH-SY5Y cells. Cell viability, protein and gene expressions were determined by the real-time cell analysis (xCELLigence) system, western blotting and real-time polymerase chain reactions (Rt-PCR), respectively. Our findings suggested that MK-801 administration decreased cell survival probably via the increasing GSK-3 beta gene expression and activity in the SH-SY5Y cells. Pre-treatments with famotidine, olanzapine, and SB 415286 prevented MK-801 induced cell death via inhibitory effects on the MK-801 induced GSK-3 beta activity. Overall, the present results suggest that famotidine has a neuroprotective effect against MK-801 via modulation of the Akt/GSK-3 beta/beta-catenin signaling pathway, an important mechanism in schizophrenia neurobiology.
Keywords: Famotidine; MK-801; GSK-3 beta; SH-SY5Y; Schizophrenia; GLYCOGEN-SYNTHASE KINASE-3; NEGATIVE SYMPTOMS; SCHIZOPHRENIA; INHIBITION; NEURONS; PHARMACOTHERAPY; HALOPERIDOL; EXPRESSION; OLANZAPINE; APOPTOSIS